SIMBOLISME PRAKTIK SANTET DALAM FILM EYANG PUTRI : KAJIAN ANTROPOLINGUISTIK - Cicih Kurniasih; Ahmad Baehaki; Sirat Hendrawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Culture is not merely a custom or tradition but a system of symbols that have meaning. One example of a cultural practice that uses symbols is the practice of black magic. This study aims to examine the meanings of black magic symbols in the film Eyang Putri through Clifford Geertz's symbolic approach. The research employs a descriptive qualitative method, focusing on the film Eyang Putri, which was released in 2021. The technique used for data collection was note-taking.The data obtained consisted of tools and mantras used in black magic practices. The results of this study indicate the use of tools as intermediaries for black magic and the use of mantras to direct black magic practices towards the victims.